PREVALENSI DAN IDENTIFIKASI PENYEBAB PENYAKIT YANG MENGHAMBAT PENETASAN TELUR UDANG WINDU (Penaeus monodon Fabr) DI HATCHERI KABUPATEN TAKALAR - Tompo, Arifuddin; Sari, Andi Puspa (Jurnal Pendidikan Teknologi Pertanian, 2016)
The study was conducted in several Hatchery in Takalar which aims to find out howthe disease organisms can inhibit tiger shrimp hatcheries in some Hatchery in Takalar. Samples were taken from four Hatchery, each Hatchery taken 200 shrimp eggs that did not hatch for further microscopic testing. Identification of types of parasites such as that done by the method of Johnson (1978), Fernando et al (1972) and Kabata (1985). Identification of bacteria in eggs isolated by following the instructions Sinderman and Ligtner (1988). Results showed that of the identification results obtained types of parasites that have invested tiger shrimp eggs are Zoothamnium sp, Epistylis sp, and from the class of bacteria were found Vibrio sp. The prevalence rate Zoothamnium sp attacks by 23%, Epistylis sp, and Llegenidium sp 7.2% and amounted to 20.9%. Water quality parameters include temperature, salinity, pH, dissolved oxygen and ammonia were observed during the study is well within eligible for hatching eggs tiger prawns